European public law. The achievement and the Brexit challenge - Birkinshaw, Patrick J. (European monographs ;, 2020)
European Public Law' analyses the development of the rule of law under European influence since the 1960s and offers an extended examination of the nature of the development which has had profound practical and legal consequences for Europe and the United Kingdom (UK). The sphere of public law is ill defined and controversial. Taking the broad view that it comprises aspects of constitutional principles, good and humane administration, judicial review based on the rule of law, human rights, liability for wrongdoing, public procurement, provision of public services, transparency, social media and protection of privacy - areas that link legal control to broad governmental purposes? the third edition of this established and much-praised work expands its examination on the emergence of European public law from European Union (EU) law (and its European Community and European Economic Community antecedents), the European Convention on Human Rights and the interface of these systems with Member State systems to include the currently all-important challenge of Brexit.